Biomechanical experimental substantiation of the fixation technique of bone allograft and recipient’s bone - Vyrva, Oleg; Golovina, Yanina; Karpinska, Olena; Karpinsky, Michael (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
A technique combining bone allografting and arthroplasty — allocomposite replacement (ACR), is widely used in orthopedic oncology. However, the risk of complications after this surgical intervention remains high — non-union of the allograft with the recipient's bone, its lysis, infection. Objective: to substantiate ACR techniques biomechanically using segmental bone allografts with intramedullary fixation in the recipient’s bone. Methods: the experiment was performed on 28 male rats (age 5 months, body weight 350–400 g). ACR of the femur was modeled with transverse (I group) and stepcut (II) osteotomy. The strength of the isolated preparations of the operated animal femurs was examined on a biomechanical stand after 3 and 6 months after the surgery. Digital indicators are processed statistically. Results: in the Ist group of animals (3 months after surgery) the strength of the operated bones was statistically significantly lower compared to the contralateral (t = –2.674; p = 0.037), and in rats with stepcut osteotomy the difference was not significant. In 6 months after surgery, bone strength with stepcut osteotomy was found to be (44.3 ± 15.6) N greater than with transverse (t = –2.838; p = 0.023). At the same time, the strength of the operated bones of animals of the Ist group was comparable with that of the contralateral limbs (t = –1.279; p = 0.248), and in the IInd exceeded them (t = 6,000; p = 0.001). Conclusions: stepcut osteotomy with subsequent fixation of the bone allograft to the recipient’s bone improves the conditions for reparative osteogenesis in the area of their contact and reduces the risk of ACR complications. Bioreconstructive surgical interventions in order to replace post-resection defects of long bones in patients with tumor lesions can improve orthopedic, functional and oncological treatment results.